Impact of a Multidisciplinary Team Approach on the Diagnosis and Management of Placenta Accreta Spectrum Disorder [A228]. (May 2022) - Yao, Ruofan; Nguyen, Hoang Yen; Hong, Linda; Martin, Courtney; Balli, Kevin; Ioffe, Yevgeniya
Abstract : INTRODUCTION: Patients with suspected placental accreta spectrum (PAS) are recommended to be referred to specialized centers for antepartum management and cesarean hysterectomy. Previously, it was shown that multidisciplinary approach could improve outcomes, but evidence on referral volume and antenatal diagnostic accuracy were sparse. Our goal is to evaluate the impact of a multidisciplinary team on referral volume, diagnostic accuracy, and surgical outcomes. METHODS: This was a single-center retrospective cohort study, based in the only university-affiliated tertiary referral center within the region. Patients who underwent cesarean hysterectomy for suspected PAS from January 2014 to April 2021 were divided based on pre- and post-exposure of the multidisciplinary team in January 2019. The outcomes of interest were quantitative blood loss, blood transfusion, diagnostic accuracy, ICU admission, bladder injury, and postoperative length of stay. This study was approved by the institutional review board (#520052). RESULTS: A total of 114 patients were included in the cohort: 59 patients were from January 2014 to December 2018 and 55 patients were from January 2019 to April 2021. Since the establishment of the multidisciplinary center, there was a 1.4-fold increase in referral volume. Patients undergoing cesarean hysterectomy since the establishment of the multidisciplinary team had less quantitative blood loss ( P =.005) and required less units of packed red blood cell transfusion ( P <.001). In addition, the diagnostic accuracy improved from 35.6% to 83.6% ( P <.001). CONCLUSION: Since the establishment of the multidisciplinary team, our center experienced an increase in referral volume, improvement in antenatal diagnostic accuracy, and surgical outcomes.